Pengaruh Asimetri Informasi, Ketaatan Aturan Akuntansi, Dan Integritas Terhadap Kecenderungan Kecurangan Akuntansi (Fraud) Pada LPD Di Kecamatan Abiansemal - I Dewa Ayu Sri Prami Rahayu; I Wayan Sudiana (Hita Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of information asymmetry, compliance with accounting rules and integrity on the tendency of accounting fraud in LPD in Abiansemal Sub-district. Data were obtained from distributing questionnaires directly to respondents. The population in this study were all LPD employees in Abiansemal Sub-district, totaling 311 people. The number of samples used was 84 people, with a purposive sampling method. The analysis technique used is multiple linear regression analysis. The results of this study indicate that asymmetry of information and integrity have a positive and significant effect on the tendency of accounting fraud. On the other hand, obedience to accounting rules has no effect on the tendency of accounting fraud